DEVELOPING POCKET E-BOOK TO IMPROVE RETELLING SKILLS OF FOLKLORES FOR HIGH SCHOOL STUDENTS - Silvia Yulianti; Ahmad Fadly (SEAMEO QITEP in Language, 2023)
The primary issue addressed in this research revolves around the absence of folklore books suitable for educational purposes in high schools. Consequently, the research objective focuses on developing an e-book designed to enhance high school students' proficiency in retelling folklore narratives. Employing a Research and Development (R&D) approach, the researchers engaged in data collection and analysis, product design, validation, revisions, testing, and the eventual production of the e-book. The data for this research includes various folklore sources, namely,